2011
DOI: 10.1177/1545968311401627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Step Training and Rhythmic Auditory Stimulation on Functional Performance in Parkinson Patients

Abstract: Background. Rhythmic auditory stimulation (RAS) can influence movement during straight line walking and direction transition in individuals with Parkinson disease (PD). Objective. The authors studied whether multidirectional step training with RAS would generalize to functional gait conditions used in daily activities and balance. Methods. In a matched-pairs design, 8 patients practiced externally paced (EP) stepping (RAS group), and 8 patients practiced internally paced (IP) stepping (no RAS group) for 6 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 43 publications
6
97
0
7
Order By: Relevance
“…A common feature of these studies deals with the introduction of enhanced sensory feedback (auditory, visual or somatosensory) cues to provide augmented feedback about performance. Motor learning is enhanced by external cueing [47] whilst clinical studies have shown that externally cued practice over more extended periods (3-6 weeks) leads to significant benefits for gait and balance [48][49][50] and is more effective than interventions that do not use augmented feedback [44,51].…”
Section: Feasibilitymentioning
confidence: 98%
“…A common feature of these studies deals with the introduction of enhanced sensory feedback (auditory, visual or somatosensory) cues to provide augmented feedback about performance. Motor learning is enhanced by external cueing [47] whilst clinical studies have shown that externally cued practice over more extended periods (3-6 weeks) leads to significant benefits for gait and balance [48][49][50] and is more effective than interventions that do not use augmented feedback [44,51].…”
Section: Feasibilitymentioning
confidence: 98%
“…The effectiveness of cueing on gait (including turning) in PD is well-established, even in the patient's home environment, without increasing the risk for falls [94][95][96]. Rhythmic auditory cues even seem to reduce the interference effect of a dual task on gait [93,97]. In upper limb activities, visual cues can improve handwriting [98] and self-vocalization or auditory cues can improve the kinematics of reaching [99][100][101].…”
Section: Movement Strategy Trainingmentioning
confidence: 99%
“…Rehabilitative approaches, such as Neurologic Music Therapy (NMT) [42] refer to neuroscientific models and use primarily the potential of musical stimuli to activate perception and production areas in the human brain, providing a series of therapeutic applications to sensory, cognitive, and motor dysfunctions resulting from neurological disorders. Using directive approach based on a series of exercises, NMT may be used, for example, to improve gait and movements in post-stroke and PD patients [43][44][45][46][47] and language in persons with aphasia [48,49] . On the other hand, simple music listening interventions don't require neither a specifically trained therapist nor a direct therapeutic relationship with the patient being that beneficial effects are induced by the content of the musical stimuli and by the activity of listening itself.…”
Section: Music Therapymentioning
confidence: 99%